Influence of educational level on test and treatment for incident hypothyroidism. (7th February 2021) - Møllehave, Line Tang; Jacobsen, Rikke Kart; Linneberg, Allan; Skaaby, Tea; Knudsen, Nils; Jørgensen, Torben; Kårhus, Line Lund; Kriegbaum, Margit; Grand, Mia Klinten; Siersma, Volkert; Lind, Bent; Andersen, Christen Lykkegaard; et al.
Abstract: Objective: The incidence of hypothyroidism is not expected to differ by socioeconomic factors. However, the decision to test and initiate treatment may differ. We aimed to examine whether educational level influences the probability of thyroid stimulation hormone (TSH)‐measurement and initiation of levothyroxine treatment. Design: Citizens in the greater Copenhagen Area during 2001‐2015 were included. Individual‐level data on educational level, diagnoses, GP‐contact, TSH‐measurement and medication were derived from administrative and healthcare registers. The relative risks (RR) between educational levels of annual TSH‐measurement and treatment initiation following a TSH‐measurement were analysed in Poisson regression models with generalized estimation equations. Results: A TSH‐measurement was performed in 19% of 9, 390, 052 person years. The probability of TSH‐measurement was higher with short (RR 1.16 [95% CI 1.15–1.16]) and medium (RR 1.11 [95% CI 1.06–1.12]) compared with long education. Treatment was initiated after 0.8% of 2, 049, 888 TSH‐measurements. For TSH < 5 mIU/L, RR for treatment initiation ranged between 0.47 (95%CI 0.39–0.57) and 0.78 (95%CI 0.67–0.91) for short and medium compared with long education. For TSH 5–10 mIU/L, there was no statistically significant difference. For TSH > 10 mIU/L, RR was 1.07 (95% CI 1.02–1.12) for short and 1.08 (95% CI 1.03–1.13) for medium compared with long education. Conclusion: The probability of TSH‐measurement was higher with shorter education, and the probability of treatment initiation with TSH > 10 mIU/L was marginally higher with short‐medium education compared with long education. However, the probability of treatment initiation with TSH < 5 mIU/L, that is treatment incongruous with guidelines, was substantially higher in persons with long education.